Holub József és a Tagányi-könyvtár Pécsre kerülése: Egy „vidéki” történészprofesszori egzisztencia lehetőségfeltételei az 1920-as évek elején (III. közlemény) - Szeberényi, Gábor (Per Aspera ad Astra, 2016)
In the last part of his paper the author covers those general circumstances and issues which characterized the infancy of József Holub’s career as a professor in Pécs. One of the most important factor which put Holub as a professional historian at a disadvantage in Pécs – after all those years he spent in the capital as a highly involved member in his profession’s system of relations – came from the lack of a proper research library at the newly reestablished Elisabeth University. The author – mostly via previously unknown primer historical sources – proves that Holub’s formerly accumulated social capital (and Holub himself ) played a central part in the process which led to the purchasing of Károly Tagányi’s books for the university library, after the death of the owner in 1924–1925. The historiography of Tagányi – who was one of the most influential though relatively overshadowed „master historian” for the younger generation of Hungarian historians and especially the centres of his special interests related to medieval social and legal history shown in his book collection as well – were prominently important for Holub’s own historiography. Thus, the purchasing of Tagányi’s library made an important part in establishing Holub’s existence as historian in Pécs.